Revitalization Of Learning Loss in Moji level Intermediate of Japanese Language Education Program Brawijaya University - Indrowaty, Sri Aju; Setiawati, Eti; Dewandono, Wiranto Aji; Sachputra, Sofyan Sukrian; Febrianda, Sony Difa (Chi e Journal of Japanese Learning and Teaching, 2024)
This study explores the learning loss experienced at the Moji Intermediate level within the Japanese Language Education Study Program during the COVID-19 pandemic. Over a period of two years, traditional face-to-face learning was replaced by online instruction, which affected the implementation of certain learning stages, such as kanji writing exercises conducted in the classroom. This research aims to identify the extent of learning loss during online learning, specifically with kanji writing skills at the Moji Intermediate level. A descriptive qualitative method was used, comparing course grades from both online and offline learning periods. According to Rajesh, Hasibuan, Susanto, Solihat et al. (2022), while learning loss has been widely studied with various approaches, few have addressed its impact on specific courses, particularly in Japanese language education. The findings reveal that online learning significantly reduced students' kanji writing abilities. As a result, teachers must adopt new strategies to compensate for this gap and ensure that students perform well on the Japanese Language Proficiency Test (JLPT), which is essential for graduation from the Japanese Language Education Study Program.